Evaluation of the physical-chemical properties of blueberries from diferente geographic origin - Matos, Susana (2014)
Blueberries are very popular for their potential health benefits around the world, from USA to Asia and to the Mediterranean. In the present work blueberries from cultivar Bluecrop harvested in different regions of Portugal (Estarreja-ES, Vouzela-VZ, Vila Verde-VV, Sever do Vouga-SV and Oliveira do Hospital-OH) were analysed to evaluate their physical-chemical properties: moisture content, total soluble solids (ºBrix) acidity, calibre, colour and texture. Moisture was evaluated by drying until constant weight, sugar content by refractometry and acidity by titration. Calibre was evaluated with a caliper rule, colour with a colorimeter in the CIELab colour space, and texture with a texturometer by measuring force in compression with a 2 mm probe P/2. The results showed that the sample VV had the highest moisture content as compared to all other varieties (83%), whereas the sample OH showed the highest acidity (0.79 mg citric acid/100g) and the sample ES the highest total soluble solids content (14,65 ºBrix). The average calibre ranged from 0.90 cm for sample SV to 1.17 cm for sample OH. Regarding the colour parameters it was observed that lightness (L*) was under 50, thus indicating that the samples are dark, whereas a* was around 0, so neither red nor green and b* was negative in all cases, so the colour is blue instead of yellow. The values of L* ranged from 31.07 to 36.79, respectively for samples VV and VZ; a* ranged from -0.02 to 0.62, respectively for samples VZ and VV; b* ranged from -7.76 to -5.02, respectively for samples ES and OH. The skin firmness varied from 11.0 N to 15.1 N, respectively for samples VZ and SV, while elasticity varied from 2.18 mm in the sample ES to 2.54 mm in the sample SV.